The 13th man: A woman. Inequity in professional football leadership hiring - Brusoe, C. (Leadership Education Capstones, 2017)
This is a study of gender inequity in professional leadershipwithin NFL organizations. Five former and fivecurrent employeesinvolved in the hiring process of NFL organizations were surveyed and offered insight into hiring practices and a breakdown of gender equality within the NFL.